Revisiting Technology Acceptance in School Counseling Practice: Insights from TAM Literature - Nurdiana Nurdiana; Farida Kurniawati (KONSELOR, 2026)
Technology integration in school counseling has grown, yet counselors’ acceptance varies across studies and remains under-synthesized. This systematic review explores technology acceptance in school counseling through the Technology Acceptance Model (TAM). Using the PRISMA framework, we analyzed 13 empirical studies published from 2016 to 2026, selected from multiple academic databases. A thematic synthesis examined counselors’ views on technology, factors influencing acceptance, and implementation hurdles. Results show that counselors generally view technology favorably, mainly for administrative tasks, communication, and ensuring service continuity. Nonetheless, positive perceptions did not always lead to wider adoption, particularly in direct counseling. Influencing factors include digital skills, self-efficacy, institutional support, and ethical issues, indicating that acceptance varies by task and context. This review affirms TAM's usefulness in understanding counselors’ tech acceptance and highlights how professional, institutional, and ethical factors influence implementation—explaining why positive perceptions don’t always lead to sustained use.